Gaseous nitriding of Co-10 at% and -15 at% Cr alloys at 400 °C and 450 °C - Akhlaghi, Maryam; Hock, Rainer; Dallmann, Johannes; Krapf, Anna; Merle, Benoit; Hofsäss, Hans; Körner, Carolin; Leineweber, Andreas (Journal of Alloys and Compounds, 2022)
Co-10 at% and -15 at% Cr with the stable hexagonal close packed (hcp) crystal structure at room temperature have been subjected to gaseous nitriding treatment using nitriding temperatures of 400 °C and 450 °C far below the austenite start temperature. Using X-ray and electron backscatter diffraction (EBSD), structural changes as a result of nitrogen incorporation into the initial hcp lattice can be divided into the following steps: (i) expansion of the lattice due to N uptake yielding hcp (hcpexp) at nitriding temperature of 400 °C, (ii) gradual transformation of hcpexp into an expanded face-centered cubic phase (fccexp) by increasing time at 400 °C/ or temperature to 450 °C (mixture of two phases), (iii) development of stable nitrided layer containing fccexp using moderate nitriding times up to 3 h at 450 °C and (iv) decomposition of fccexp layer into CrN nitrides and less expanded austenite and the reverse transformation from fcc to hcp at near-surface regions at 450 °C after prolonged nitriding time of 24 h. Due to occurrence of step (iv), the square-root treatment-time dependence of the nitrided layer thickness breaks down. Nitrogen-depth profiles obtained for Co-15 at% Cr by glow-discharge optical emission spectroscopy (GDOES) along with the Non-Rutherford MeV proton backscattering spectrometry reveal a nitrogen supersaturation of around 20 at% at surface-adjacent areas in hcpexp. A relatively large unit volume expansion has been recognized for hcpexp with a change of c/a ratio of around 0.6%. Hardness-depth profiles obtained for nitrided Co-10 at% and -15 at% Cr alloys using nanoindentation evidence an increase in hardness inside the nitrided layer, compared to the untreated core.
Keywords: Nitride materials; Precipitation; Phase transitions; Rutherford backscattering; scanning electron microscopy; SEM; X-ray diffraction